Description of new species of oak leaf-miners (Lepidoptera: Nepticulidae), with notes on the species groups of Stigmella Schrank associated with Quercus as a host-plant - Stonis, Jonas R.; Diškus, Arūnas; Remeikis, Andrius; Navickaitė, Asta; Rocienė, Agnė (Zootaxa, 2013)
Stigmella acuta Diškus, Navickaitė & Remeikis, sp. nov., a new species of oak-feeding leaf-miner belonging to the S. hemargyrella group, and S. cornuta Rocienė & Stonis, sp. nov., belonging to the newly designated S. cornuta group, are described from Asia and, for the first time, the S. hemargyrella group is associated with Quercus as a host-plant. The new species are illustrated with photographs of the leaf mines, adults, and genitalia. Diagnostics and host-plant preferences of seven Stigmella species groups associated with oaks (the S. caesurifasciella, S. saginella, S. quercipulchella, S. ruficapitella, S. castanopsiella, S. hemargyrella and S. cornuta groups) are discussed.